Individualised treatment for multidrug‐resistant tuberculosis in New South Wales, Australia. (26th July 2021) - Chang, Vicky; Ling, Raphael; Velen, Kavindhran; Fox, Greg
Abstract: Objective : Multidrug‐resistant tuberculosis (MDR‐TB) presents a major global health challenge. In high‐income countries, treatment is individualised to optimise efficacy and reduce toxicity. We aimed to evaluate the outcomes of patients with MDR‐TB receiving individualised antibiotic therapy in Australia. Methods : This retrospective cohort study was performed in the city of Sydney in Australia and included patients diagnosed with bacteriologically confirmed MDR‐TB diagnosed between 2000 and 2016. The clinical characteristics of patients and treatment details were extracted from medical records. The incidence of adverse events and end‐of‐treatment outcomes were also evaluated. Results : Fifty‐five patients with MDR‐TB were identified at TB clinics in seven hospitals. The median age was 32 years (interquartile range [IQR]: 27–36 years). The median duration of the intensive phase treatment was six months (IQR 6–7 months). All patients' treatment administration was directly observed. The commonest reported adverse event was ototoxicity (44%; 23/52) and successful treatment outcomes were achieved by 95% (52/55) of patients. Conclusion : This study demonstrated the high treatment success rate that can be achieved using individualised treatment for MDR‐TB in a well‐resourced setting. Implications for public health : The expansion of individualised therapy promises to contribute to MDR‐TB control and advance the ambitious goal of TB elimination by 2035.